2021
DOI: 10.1021/acsami.0c20079
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically Optimized Electrical and Thermal Transport Properties in Copper Phthalocyanine-Based Organic Small Molecule with Nanoscale Phase Separations

Abstract: A series of copper phthalocyanine (CuPc)-based organic small molecules were prepared through vapor-phase reaction. Nanoscale phase separation was observed with tunable CuPc and copper phthalocyaninato iodide (CuPcI) phase content by changing the iodine ratio. The Seebeck coefficient of the samples was significantly enhanced, which is considered to be attributed to the enhanced surface polarization effect due to the formation of a great number of nanoscale interfaces between the CuPc phase and the CuPcI phase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…[ 42–44 ] The single‐crystalline CuPc exhibits a high carrier mobility (≈40 cm 2 V −1 s −1 ) and a high Seebeck coefficient (≈900 µV K −1 ). [ 45,46 ] An ultra‐low κ of ≈0.15 W m −1 K −1 was reported for the CuPc pellet. [ 47 ] In this work, we demonstrate that CuPc nanoparticles can be exploited to effectively improve the TE performance of BST compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[ 42–44 ] The single‐crystalline CuPc exhibits a high carrier mobility (≈40 cm 2 V −1 s −1 ) and a high Seebeck coefficient (≈900 µV K −1 ). [ 45,46 ] An ultra‐low κ of ≈0.15 W m −1 K −1 was reported for the CuPc pellet. [ 47 ] In this work, we demonstrate that CuPc nanoparticles can be exploited to effectively improve the TE performance of BST compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the carrier mobility and Seebeck coefficient of the CuPc single crystal reached ∼40 cm 2 V –1 s –1 and ∼10 3 μV K –1 , respectively, much higher than those of typical conducting polymers. As for the metal phthalocyanines, it has been reported that their large Seebeck coefficient is up to 1.3–1.9 mV K –1 and charge carrier mobility is over 10 cm 2 V –1 s –1 . These discoveries encouraged ones to explore the feasibility of metal phthalocyanine as alternative TE materials. However, the carrier concentration of pristine metal phthalocyanine is usually in the range of 10 15 –10 16 cm –3 , several orders lower than those of inorganic TE materials, which results in poor electrical conductivity and low ZT value.…”
Section: Introductionmentioning
confidence: 99%